Penerapan Sistem Informasi Administrasi Kependudukan Pada Kantor Distrik Merauke - Siti fatimah Salam; Vinsensius Boli; Etha, Coleta Maskikit (Jurnal Administrasi Karya Dharma, 2023)
This study aims to find out how the population administration information system works at the Merauke District Office. The population administration information system is an information system developed based on population administration service procedures by implementing information and communication technology systems to organize the population administration system in Indonesia. In this study, researchers used a qualitative research method, namely a research method that requires an in-depth understanding and clearly describes the population administration information system at the Merauke District Office. From the results of the study it can be concluded that the population administration information system at the Merauke District Office in improving accessibility, quality and skills and an effective planning process at the Merauke District Office is sufficient but still has to improve accessibility, quality and skills by providing the best service for the community, and administrative improvements as well as in terms of human resources at the Merauke District Office need to be improved by participating in training related to the population administration information system itself. His suggestion for employees of the Merauke District Office should always prioritize the interests of their duties and functions as a state apparatus, and always be responsible for their work, it is necessary to improve adequate facilities and infrastructure so as to support population administration information system services at the Merauke District Office.